Perbedaan Penafsiran Taksiran Berat Janin Menggunakan Tinggi Fundus Uteri dengan Ultrasonografi: Differences in Interpretation of Fetal Weight Estimates Using Uterine Fundal Height with Ultrasonography - Sudirman, Jumrah; Amriani; Suriani B (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2024)
Introduction : Uterine fundal height has a strong and significant relationship with the baby's weight and reflects fetal growth and fetal size more accurately. Perinatal deaths in low birth weight births and morbidity due to large birth weights are a separate problem in perinatal health and delivery management. Estimated intrauterine fetal body weight has an important meaning in labor management.Method The research method used is Cross-Sectional. The sample in this study was 48 pregnant women who had their pregnancy checked at the Watampone Community Health Center. The sample collection technique was carried out by accidental sampling. Data analysis used the independent T test. Result which was obtained through the independent T test using SPSS, namely P value = 0.001 < 0.05. This shows that there are differences in the interpretation of fetal weight using uterine fundal height measurements and ultrasonography Conclusion There is a difference in the results of TBJ examination using the two methods, namely uterine fundal height measurements and ultrasonography, but the difference between the two is not too big.